Effect of desiccant isotherm on the performance of desiccant wheel - Chung, Jae Dong; Lee, Dae-Young (ELSEVIER SCI LTD, 2009)
Numerical simulation has been conducted for the desiccant wheel, which is the crucial component of a desiccant cooling system. As the key operating/design parameters, the rotation speed and the area ratio of regeneration to dehumidification have been examined for a range of regeneration temperature from 50 degrees C to 150 degrees C. Optimization of these parameters is conducted based on the wheel performance evaluated by means of Moisture Removal Capacity (MRC). Simulations are focused on the effect of desiccant isotherm on the optimal conditions of these operating/design parameters. Also the effects of the outdoor air temperature and humidity on the optimum design parameters are examined. (C) 2009 Elsevier Ltd and IIR. All rights reserved.
Keywords: MASS-TRANSFER; DEHUMIDIFICATION; HEAT; SIMULATION